Cover Picture: Cerium‐Complex‐Catalyzed Oxidation of Arylmethanols under Atmospheric Pressure of Dioxygen and Its Mechanism through a Side‐On μ‐Peroxo Dicerium(IV) Complex (Chem. Eur. J. 12/2016). Issue 12 (11th February 2016) - Paul, Mitali; Shirase, Satoru; Morimoto, Yuma; Mathey, Laurent; Murugesapandian, Balasubramanian; Tanaka, Shinji; Itoh, Shinobu; Tsurugi, Hayato; Mashima, Kazushi
Abstract : A cerium complex with a dianionic pentadentate ligand acted as a catalyst for aerobic oxidation of arylmethanols, in which a dinuclear cerium(IV) side‐on peroxo complex was the key intermediate. The corresponding trivalent complex was able to activate dioxygen, and the oxidation proceeded catalytically under atmospheric pressure with inexpensive and environmentally friendly dioxygen as the primary oxidant. More information can be found in the Full Paper by K. Mashima, H. Tsurugi et al. onpage 4008 ff.